New Issues, New Results The OECD's Second Survey of the Macroeconomic Costs of Reducing CO2 Emissions - Hoeller, Peter (OECD Publishing, 1992)
This paper surveys empirical studies of the costs of reducing carbon dioxide emissions. It updates and extends an earlier paper, which focused on baseline emission scenarios and the aggregate cost of emission reductions. It attempts to explain some of the differences in simulation results and highlights some major policy issues ...
Keywords: Economics